Volume 3: Controls, Diagnostics and Instrumentation; Cycle Innovations; Marine 2010
DOI: 10.1115/gt2010-22402
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Selections for Multi-Component Gas Path Diagnostics Using Analytical Approach and Measurement Subset Concept

Abstract: Gas path analysis (GPA) is a powerful tool to predict gas turbine degradations based on measurement parameters of gas turbine engines. Accordingly, prudent measurement selections are crucial to ensure accurate GPA predictions. This paper is intended to investigate the influence of measurement parameter selection towards the effectiveness of GPA algorithm. An analytical methodology for measurement selection, combined with measurement subset concept, is developed to properly select measurements for multiple comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The secondary air taken from the gas generator compressors serve as cooling and sealing air. The gas turbine has six main gaspath components, including an intermediate-pressure compressor (IPC), a high-pressure compressor (HPC), a combustion chamber, a high-pressure turbine (HPT), an intermediatepressure turbine (IPT), and a power turbine (PT) [25]. Three-shaft industrial gas turbine configurations are shown in Figure 1.…”
Section: Case Enginementioning
confidence: 99%
“…The secondary air taken from the gas generator compressors serve as cooling and sealing air. The gas turbine has six main gaspath components, including an intermediate-pressure compressor (IPC), a high-pressure compressor (HPC), a combustion chamber, a high-pressure turbine (HPT), an intermediatepressure turbine (IPT), and a power turbine (PT) [25]. Three-shaft industrial gas turbine configurations are shown in Figure 1.…”
Section: Case Enginementioning
confidence: 99%
“…The initial population is 20, the maximum generation G is 200, the terminal number G end for iteration is 30, the initial crossover probability P c0 is 0.9, and the initial mutation probability P m0 is 0.04. The value range of the regularization parameter is (2 À10 -2 10 ) and the initial value is 1. The value range of the kernel parameter is (2 À5 -2 5 ) and the initial value is 0.1.…”
Section: Monitoring Modulementioning
confidence: 99%
“…Currently, several approaches related to searching for optimal sensor suites have been proposed by different scholars. [10][11][12] Regardless of the method chosen for measurement, the main aim is to provide optimal sensors for gas turbine engine health monitoring and fault diagnosis. However, as critical components, sensors are also prone to fail by themselves, especially those along the gas path bearing high temperature, high pressure, and radiation in extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity norm which describes the overall sensitivity of each sensor can then be expressed using Eq. ( 4) below (Jasmani et al, 2010).…”
Section: Sensor Selectionmentioning
confidence: 99%